Pyruvate dehydrogenase kinase regulates macrophage polarization in metabolic and inflammatory diseases - Li, Chenyu; Liu, Chuanbin; Zhang, Junfeng; Lu, Yanyu; Jiang, Bingtong; Xiong, Huabao; Li, Chunxia (Frontiers in Immunology, 2023)
As an important cell type in the innate immune response system, macrophages possess the characteristics of high heterogeneity, plasticity, and pluripotency. The two distinct macrophage phenotypes have different metabolic pathways and functions in inflammation-related diseases: M1 macrophage energy metabolism is dominated by glycolysis of glucose to lactate, whereas M2 macrophages rely on the oxidative phosphorylation metabolic pathways. Understanding the regulation of macrophage polarization is vital as it changes depending on the intracellular metabolic reprogramming. However, the detailed metabolic pathways regulating macrophage polarization and function remain unclear. Pyruvate dehydrogenase kinase (PDK) regulates pyruvate oxidative decarboxylation by inhibiting pyruvate dehydrogenase complex activity via phosphorylation and further links glycolysis with macrophage metabolism. In recent years, increasing evidence has shown that PDK is commonly associated with the metabolism and polarization of macrophages in metabolic and inflammatory diseases. This review examines the relationship between PDK and macrophage metabolism and discusses the mechanisms by which PDK regulates monocyte/macrophage polarization, migration, inflammatory cytokine secretion, and energy metabolism in metabolic and inflammatory diseases. Elucidating the relationships between the metabolism and polarization of macrophages under physiological and pathological conditions as well as the regulatory pathways involved may provide valuable insights into the in-depth understanding of the etiology and treatment of macrophage-mediated inflammatory diseases.